Comparison between radiographic and ultrasound angle measurements in the assessment of idiopathic scoliosis - Samra Pjanić; Goran Talić; Dragana Bojinović-Rodić (Биомедицинска истраживања, 2021)
Introduction: Radiological assessment is still being considered a golden standard when it comes to detection, follow-up and treatment of idiopathic scoliosis. However, it has universally been proven that radiation is cumulative and that it has oncogenic effects. For this reason, nowadays it is becoming increasingly popular to perform spinal ultrasounds using the Scolioscan® device. Relevant research has shown diagnostic potential of the device and its application in the assessment and monitoring of idiopathic scoliosis. The aim of our study has been to compare angle measurements in ultrasound and radiological spinal images and to determine the role of ultrasound in the assessment process and follow-up of patients with idiopathic scoliosis. Methods: This cross-sectional study has been conducted on a sample of 172 patients. Its participants are boys and girls, patients of the Team for Scoliosis that operates within the Department for Habilitation and Rehabilitation of Children in the Institute for Physical Medicine and Rehabilitation ''Dr Miroslav Zotović'', Banja Luka, the Republic of Srpska. Radiography and ultrasound of the spine have been performed on every patient on the same day. Three specially trained operators administrated the ultrasound scanning, while four raters (i.e. doctors) measured the radiographic Cobb angle and the ultrasound Scolio angle. Patients have been divided into groups according to gender, curve location and curve severity. Results: In general, ultrasound angles are shown to be smaller compared to Cobb angles, which has been confirmed in previous studies as well. The mean difference between Cobb and Scolio angle is statistically, but not clinically significant (3.62±4.39°, p<0.001). There is a statistically significant good positive correlation between the Cobb and the Scolio angle (r=0.675, p<0.001). According to groups, our results indicate a better correlation in the girls group (r=0.688, p<0.001) as opposed to the boys group (r=0.632, p<0.001). The same holds true for the thoracic group (r=0.736, p<0.001), compared to the (thoraco) lumbar group (r=0.654, p<0,001). A stronger correlation can also be seen in the group with a Cobb angle that is equal to or higher than 20° (r=0.518, p<0.05) than in the group with a Cobb angle lower than 20° (r=0.462, p<0.001). Conclusion: The results of our study confirmed a good validity of the ultrasound method using the Scolioscan® device, compared to conventional radiography, taking into account clinically insignificant differences in angle measurements. Using only B-mode ultrasound images - with no additional software analysis, nor 3D reconstruction of spinal deformities - proved to be sufficient for a follow-up of scoliosis, with respect to other parameters, such as clinical assessment, back surface topography, etc.
Keywords: idiopathic scoliosis; ultrasound; radiography; imaging